Inflammatory cells in the ascending aortic aneurysm in patients with type 2 diabetes versus patients with hypertension - Aleksandra Milutinović; Ruda Zorc-Pleskovič (Biomolecules & Biomedicine, 2022)
Aortic aneurysms occur relatively frequently in the ascending thoracic aorta, but are rarely seen in patients with type 2 diabetes. Our aim was to evaluate inflammatory cell infiltration in the ascending aortic aneurysm wall in patients with diabetes without arterial hypertension (DM2 group, N=6) versus hypertensive non-diabetic patients (AH group, N=34). For histologic analysis, the sections were stained with hematoxylin-eosin and Movat pentachrome. The immunohistochemical staining was used to analyze the infiltration of pro-inflammatory (CD68) and anti-inflammatory macrophages (CD163), T helper (CD4) and T killer cells (CD8), and B (CD79a) and plasma cells (CD138) in all three layers of aneurysms of both groups. The statistical significance of the differences between groups was evaluated by ANOVA and the Welch test.